2022
DOI: 10.1021/acsnano.2c01788
|View full text |Cite
|
Sign up to set email alerts
|

Current-Induced Magnetization Switching Across a Nearly Room-Temperature Compensation Point in an Insulating Compensated Ferrimagnet

Abstract: Insulating compensated ferrimagnets, especially hosting room-temperature compensation points, are considered promising candidates for developing ultra-high-density and ultrafast magnonic devices owing to combining the characteristics of both ferromagnets and antiferromagnets. These intriguing features become outstanding close to their compensation points. However, their spin–orbit torque (SOT)-induced magnetization switching, particularly in the vicinity of the compensation points, remains unclear. Herein, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 41 publications
(83 reference statements)
0
11
0
Order By: Relevance
“…Recently, it has been reported that the sign of the AHE in REIG/Pt changes when crossing T M . 31,38 This simple method combined with diverging H c behavior thus offers an ideal platform to detect T M when AHE is finite.…”
Section: Magnetic Compensation Temperaturementioning
confidence: 99%
“…Recently, it has been reported that the sign of the AHE in REIG/Pt changes when crossing T M . 31,38 This simple method combined with diverging H c behavior thus offers an ideal platform to detect T M when AHE is finite.…”
Section: Magnetic Compensation Temperaturementioning
confidence: 99%
“…Harmonic Hall voltage (HHV) [ 4,19,20,50 ] and spin–torque FM resonance [ 51 ] measurements are the two established methods in this context but rely on the Hall resistance and magnetoresistance output signals, respectively, which are orders of magnitude smaller in HM/MI systems with respect to all‐metallic systems. The few existing studies have considered only the damping‐like (DL)‐SOT characterization, [ 4,50,52–54 ] but the separate quantification of the field‐like (FL)‐SOT, equally important for the SOT‐driven magnetization dynamics, [ 55–60 ] and a proper account of current‐induced Joule heating in these measurements and interfacial spin transport properties remained elusive thus far.…”
Section: Introductionmentioning
confidence: 99%
“…(DL)-SOT characterization, [4,50,[52][53][54] but the separate quantification of the field-like (FL)-SOT, equally important for the SOTdriven magnetization dynamics, [55][56][57][58][59][60] and a proper account of current-induced Joule heating in these measurements and interfacial spin transport properties remained elusive thus far.…”
Section: Introductionmentioning
confidence: 99%
“…Ultrafast spin modulation of magnetic materials by femtosecond (fs) laser has been a hot issue for the last two decades since it breaks through the picosecond (ps) limit of magnetic writing and can be used for ultrafast magnetic recording. The antiferromagnets (AFM), due to the absence of a net angular momentum, should lead to orders of magnitude faster spin dynamics and are conducive to developing ultrahigh-speed magnetic memories. Experimentally, the investigation of the spin dynamics for AFM is practically challenging due to zero net magnetization. Normally, the rare-earth transition metal (RE-TM) ferrimagnets (FIM), with their antiferromagnetically coupled sublattices and a nonzero net magnetic moment, could replace the AFM as good candidates for the spin dynamics. …”
Section: Introductionmentioning
confidence: 99%